MEASURING ATTITUDE TOWARDS MUTUAL FUND INVESTMENT DECISIONS: EVIDENCES FROM TRIPURA, INDIA - Singh, Ranjit; Deb, Sujit; Pandiya, Bhartrihari; Gope, Arjun (Indian Journal of Finance and Banking, 2021)
The purpose of this paper is to assess the attitude of bank employees in Tripura towards investment in the mutual fund and investigate the impact of attitude on volume of investment. The study methodology is based on the responses of a questionnaire received from 262 employees of banks in Tripura. On the basis of primary data, the attitude of the employees has been assessed and ordinal logistic regression is used to find out the impact of attitude on their volume of investment in mutual fund. It is found that overall attitude of bank employees in Tripura towards investment in mutual fund is favorable. It can also be concluded that attitude and volume of investment in mutual fund is positively related. The study is useful for the fund managers of mutual funds. Once the attitude to employees towards investment in mutual fund is ascertained, then suitable strategy regarding imparting training can be designed to improve attitude towards investment in mutual fund. The study is original in nature. JEL Classification Codes: D63, D25.